2022
DOI: 10.26858/pjppsd.v2i4.37337
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Penggunaan Media Pembelajaran Interaktif Berbasis Powtoon Terhadap Hasil Belajar Matematika Siswa Kelas IV SD

Abstract: This research is a type of quantitative research with a pre-experimental research design. The purpose of this study was to determine students' mathematics learning outcomes and to determine whether or not there were significant differences before and after the use of powtoon-based learning media. The results showed that there were significant differences before and after learning using Powtoon-based learning media on the Mathematics learning outcomes of fourth grade students of SD Inpres 6/75 Bukaka, Bone Rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This study found that teachers use manipulatives in a variety of ways, including introducing new concepts, reinforcing learning, and providing hands-on activities (Aryanti et al, 2022) . The use of manipulatives turns out to have several benefits, including increasing students' understanding of mathematical concepts, increasing student involvement in the learning process, and supporting the inclusion of students with diverse learning needs (Apriana et al, 2020) . However, teachers also face several challenges using manipulatives, including limited resources and training, difficulty adapting manipulatives for different learning needs, and time constraints (Murni et al, 2022) .…”
Section: Resultsmentioning
confidence: 99%
“…This study found that teachers use manipulatives in a variety of ways, including introducing new concepts, reinforcing learning, and providing hands-on activities (Aryanti et al, 2022) . The use of manipulatives turns out to have several benefits, including increasing students' understanding of mathematical concepts, increasing student involvement in the learning process, and supporting the inclusion of students with diverse learning needs (Apriana et al, 2020) . However, teachers also face several challenges using manipulatives, including limited resources and training, difficulty adapting manipulatives for different learning needs, and time constraints (Murni et al, 2022) .…”
Section: Resultsmentioning
confidence: 99%
“…Then research conducted by Yatini (Maulana, 2019), stated that the use of ICT-based learning media has proven to be very effective in increasing student participation and achievement. However, it is important to remember that the effectiveness of using ICT-based learning media will achieve maximum results if there is no support from various parties.…”
Section: Introductionmentioning
confidence: 99%